Primary School EFL Teachers’ Practices and Views of Technology-Enhanced Differentiated Instruction: A Pilot Interview Study - Kótay-Nagy, Annamária (Working Papers in Language Pedagogy, 2022)
Recent years have seen a growing interest in the concept of technology-enhanced differentiated instruction (TEDI). Yet, to date, little is known about how TEDI may be used in the teaching of English as a foreign language (EFL). The present small-scale qualitative study sought to address this research gap by developing and piloting an interview schedule suitable for use in exploring EFL teachers’ self-reported practices and views of TEDI. Furthermore, the study aimed to gain an initial understanding of the collected data. Five primary school EFL teachers who use technology on a frequent basis were interviewed, and following two rounds of adjustments, the questions were deemed capable of eliciting sufficient information. The results emerging from the thematic analysis of the data show that technology may be used in various ways to differentiate the content, the process, and the product of teaching. TEDI also offers benefits both for students and teachers, such as the enhancement of self-paced learning and formative assessment. Although the participants voiced a few concerns too, they expressed an overall positive attitude towards TEDI. The results confirm that technology may be suitable for supporting differentiation in the EFL class and call for a more in-depth examination of TEDI practices.